KEPENTINGAN NORWEGIA MENDUKUNG PROGRAM REDUCING EMISSION FROM DEFORESTATION AND DEGRADATION (REDD) DI HUTAN AMAZON PERU TAHUN 2014 - Eko Novrialdi; Indra Pahlawan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This research describes the interest of Norway supporting the Reducing Emissions from Deforestation and Degradation (REDD) program in the Peruvian Amazon in 2014. Norway supports this program through a Letter of Intent (LOI) in cooperation to reduce emissions from deforestation and degradation in Peruvian Amazon and environmentally sustainable development in Peru. Norway supports this program with gradually funding system until 2020 . The method that is used in this research is qualitative research. Some of the datas are obtained from books, journals, articles, internet and other media. This research focuses describes the interest of Norway supporting the REDD program in the Peruvian Amazon. Using constructivist perspective, foreign policy by Graham T. Allison and national interest concept by Donald E. Nuchterlain, this research will find out the interest of Norway supporting the REDD program in the Peruvian Amazon. The impact of climate change are already being felt in Norway. Norway ratified the Kyoto Protocol and REDD be an alternative solution of the obligation to reduce emissions without sacrificing the domestic industry. Since become a world leader in climate change issues, Norway has a good image of the climate change issues. This good image can be used by Norway to sell environmental technologies to the consumptive country. And last, Norwegian financial assistance to Peru can strengthen the bilateral cooperation, especially in the economic field. Keywords: REDD, Peruvian Amazon, Interest.